Study of the influence of a powerful pulsed ion beam on titanium deeply-doped with aluminum; Vacuum; Vol. 217 - Ryabchikov A. I. Aleksandr Ilyich; Korneva O. S. Olga Sergeevna; Ivanova A. I. Anna Ivanovna; Chernyshev A. A. Artem Alekseevich; Tarbokov V. A. Vladislav Aleksandrovich (2023, 2023)
The work studies the synergy effect of high-intensity implantation of aluminum ions and the subsequent impact of a powerful pulsed ion beam on the microstructure and properties of titanium. Specimens of titanium were implanted for 1 h at a temperature of 1170 K with an ion fluence of 1021 ions/cm2 . Layers with a thickness of about 150 μm were obtained. The energy impact was carried out by a powerful nanosecond pulsed ion beams with an ion current density on the target of 100 A/cm2. The paper presents data on changes in the elemental composition, and microstructure of ion-doped and energy-modified layers. It has been established that the additional energy impact on the ion-doped layer of a powerful pulsed beam improves microstructure at depths of about 4.31 μm. The synergistic of high-intensity ion implantation of aluminum and the energy impact of a pulsed ion beam improves the wear resistance of titanium by eighteen folds.